"I eat two meals per day" impact of climate variability on eating habits among households in Rufiji district, Tanzania: a qualitative study. Issue 1 (December 2016) - Saronga, Naomi; Mosha, Idda; Kessy, Anna; Ezekiel, Mangi; Zizinga, Alex; Kweka, Opportuna; Onyango, Paul; Kovats, Sari
Abstract Background Improved understanding of the influence of climate variability on eating habits is required to manage health outcomes that could be produced. Agriculture production is the main source of income to people in Rufiji district, where communities produce food for household and also for income. Effects of climate variability and weather extremes include occurrence of floods and prolonged dry seasons, which are recently reported to be very frequent in Africa continent, affecting food production. Prolonged dry seasons as well as frequent floods have been reported to destroy cultivated food crops in Rufiji district. However, there is little evidence on climate variability effects on household food security and their eating habits in Tanzania. Therefore, this study assessed the influence of climate variability impacts such as prolonged dry seasons and floods on the eating habits of Tanzanian rural households. Results Study findings showed that respondents recognized changes in seasonal trends such as rainfall pattern and increase in temperature in the area. Drought and floods reduce food production and cause shortages in households. Low and poor harvest of food crops is the major contributing factor in their farms of rice and maize, the main staple food crops grown amidst prolonged dry seasons. They reported existence of household food shortage which was not there 10 years ago. Participants developed adaptation mechanisms that included reducing food quantity, eating of new meals which were not eaten before as a main meal such as cooked unripe mangoes and stiff porridge. Household members decided to change eating habits as an adaptation strategy to the situation of food shortage. Some discussants acknowledged reducing number of meals, eating two meals a day instead of three or four as it was 10 years ago. Conclusion Climate variability has led to reduced amount of annual rainfall, thus affecting food productivity and consequently food shortages and changes in dietary habits among the people in Rufiji. Additional research is warranted to assess the impacts of climate variability on nutritional quality of meals.